Fast dynamics of radiofrequency emission in FTU plasmas with runaway electrons. (3rd August 2021) - Buratti, P; Bin, W; Cardinali, A; Carnevale, D; Castaldo, C; D'Arcangelo, O; Napoli, F; Ravera, G L; Selce, A; Panaccione, L; Romano, A
Abstract: Radiofrequency emission in the 0.4–3 GHz range from FTU tokamak in presence of runaway electrons (REs) has been measured in various plasma regimes. Rapid emission bursts associated with enhanced RE pitch-angle scattering reveal kinetic instabilities affecting evolution of the RE population from the buildup phase. Such measurements also provide a sensitive monitor for instabilities during early RE formation. The leading edge of radio bursts is much shorter than interleaving periods of low emission; spectral broadening during growth indicates nonlinear wave coupling as an explanation for the observed intermittency. Both broadband and coherent spectra have been observed. Radio emission disappears at the beginning of post-disruption RE plateaus, and subsequently reappears in the shape of very intense bursts accompanied by macroscopic magnetic perturbations.